Quantitative study of the use of psychotropic medications dispensed in a public pharmacy in the city of São Miguel do Iguaçu, Paraná (Research, Society and Development, 2023)
Introduction: Access to medicines necessary for health recovery is a guaranteed right in most countries, but currently a third of the world's population does not have access to benefits that can be provided by essential pharmacological treatment. In Brazil, the population has easy access to free medicines, provided by the SUS (Unified Health System), for various diseases. Currently, the country is experiencing alarmingly growing numbers of cases of illnesses such as depression and anxiety, and the population is resorting to controlled medications in search of treatment or stability of the disease. Objective: Therefore, the present work proposes the main theme of pointing out the quantities of psychotropic medications dispensed annually to the population of São Miguel during five years, among them, one year presented was due to the Covid-19 pandemic. Materials and methods: this research was based on collecting data indicating the number of psychotropic medications dispensed by medication class, in the form of tablets, which were dispensed by the municipal basic pharmacy of São Miguel do Iguaçu, Paraná, from 2017 to 2021. Results and discussion: the municipality has high dispensing rates of controlled medications, although the population is less than 30 thousand inhabitants, mainly antidepressants, anticonvulsants, antipsychotics and benzodiazepines. Conclusion: the alarming numbers of dispensing in some years, in certain classes, were evident, raising awareness of the excessive consumption of controlled medications today, which has only been growing over the years, in all age groups.